Theodosia Burr Alston papers - Alston, Theodosia Burr, 1783-1813.
Chiefly letters of Alston to her half-brother A. J. Frederick Prevost including a letter (Dumfries, Va.; 1801 October 18) describing plague in New York, quarantine against yellow fever at Philadelphia, and visit to the U.S. Capitol and White House in Washington, D.C., a letter (Richmond, Va.; 1807 September 2) after conclusion of the trial of Aaron Burr for conspiracy shows her and his feelings at the acquittal, and letters (1792 October 20) and (South Carolina; 1809 September 12) regarding family matters. Also includes an unsigned letter (1801 January 10) and letter signed Thad (?) Burr (1789 January 5) addressed to Prevost.
Positive photostats.
Daughter of Aaron Burr. Born Theodosia Burr; married Joseph Alston, 1801.
Collection material in English.
Keywords: Burr, Aaron, -- 1756-1836.; Prevost, A. J. Frederick, -- 1767- -- Correspondence; United States Capitol (Washington, D.C.); White House (Washington, D.C.); Burr Conspiracy, 1805-1807.; Epidemics -- New York (State); Trials (Conspiracy); Yellow fever -- Pennsylvania -- Philadelphia